Representation of transsexuals in Malaysian English print media / Thiba a/p Naraina Chetty - Naraina Chetty, Thiba (2014)
The current study, in combining Butler’s (1999) performativity theory and Reisigl and Wodak’s (2009) discourse-historical approach, attempts to ascertain the discursive practices that help shape and construct the identities of Malaysian transsexuals. The study examines editorial and opinion editorials that were published in two English print media in Malaysia to understand the way argumentation schemes and linguistic means are deployed in the construction of transsexuals’ identity. The analysis of the data depicts that the print media have generally intensified the representation of transsexuals as heavily discriminated group through the use of negative and emotionally charged language. Although the articles were written in sympathetic tone, transsexuals were mostly portrayed as victims and those involved in vice trade. Besides, the same level of prominence was not provided for transsexuals and other individuals represented in the print media. It was also found that the print media have focused more on male-to-female transsexuals and have excluded female-to-male transsexuals. The analysis also shows that the print media have structured their opinions on a neutral ground when comments were made on the legal system and other issues pertaining integration of transsexual. The study concludes that the representation of transsexuals in the print media was conditioned by the socio-cultural setting in Malaysia. The way transsexuals were portrayed in the print media may have been influenced by the dominant culture. The study concludes that further studies are important to shed light on the way discourse constitutes and is constituted.